Malibu Renace - Reid, Taylor Jenkins; Bru de Sala i Marti, Marta de (Argentina : Umbriel, 2021)
"Malibu: August 1983. It's the day of Nina Riva's annual end-of-summer party, and anticipation is at a fever pitch. Everyone wants to be around the famous Rivas: Nina, the talented surfer and supermodel; brothers Jay and Hud, one a championship surfer, the other a renowned photographer; and their adored baby sister, Kit. Together the siblings are a source of fascination in Malibu and the world over--especially as the offspring of the legendary singer Mick Riva. The only person not looking forward to the party of the year is Nina herself, who never wanted to be the center of attention, and who has also just been very publicly abandoned by her pro tennis player husband. Oh, and maybe Hud--because it is long past time for him to confess something to the brother from whom he's been inseparable since birth."--Provided by publisher.
Keywords: Brothers and sisters -- Fiction; Celebrities -- Fiction; Parties -- Fiction; Summer -- Fiction; Secrecy -- Fiction; Hermanos y hermanas -- Novela; Fiestas -- Novela; Verano -- Novela; Secretos -- Novela; Celebridades -- Novela; Novels